Baseline profiles of auditory, vestibular, and visual functions in youth tackle football players - Travis White-Schwoch; Jennifer Krizman; Kristi McCracken; Jamie K Burgess; Elaine C Thompson; Trent Nicol; Nina Kraus; Cynthia R LaBella (Concussion, 2020)
Aim: Neurosensory tests have emerged as components of sport-related concussion management. Limited normative data are available in healthy, nonconcussed youth athletes. Patients & methods/results: ...